2022
DOI: 10.21744/ijhms.v5n1.1829
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged newborns and prolong pregnancy

Abstract: The article is devoted to the current problems of obstetrics, perinatology and neonatology. The article presents a literary review and covers scientific views on the factors of births and hazardous factors that lead to transfer and prolonged pregnancy. The most common perinatal complications of a delayed pregnancy are stillbirth, asphyxia, and birth trauma. Neonatal morbidity in premature infants is 29% and perinatal mortality is 19%, which is higher than in preterm infants. If the pregnancy is 43 weeks or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results of the analysis of the combination of intermittent auscultation and palpation monitoring for the problems found. Monitoring analysis of the combination of intermittent auscultation and palpation of intrapartum mothers on oxygen saturation (SpO2) of newborns (Ermatov et al, 2022;Hanasi et al, 2022). The results of the analysis of the effectiveness of monitoring the combination of intermittent auscultation and palpation as well as CTG on the problems found to prove that there is no difference in the SpO2 of the baby that is found, if during the monitoring process both use the combination method and CTG if it is found that the monitoring results experience early deceleration then the output is Newborns are thought to have decreased oxygen saturation (SpO2).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis of the combination of intermittent auscultation and palpation monitoring for the problems found. Monitoring analysis of the combination of intermittent auscultation and palpation of intrapartum mothers on oxygen saturation (SpO2) of newborns (Ermatov et al, 2022;Hanasi et al, 2022). The results of the analysis of the effectiveness of monitoring the combination of intermittent auscultation and palpation as well as CTG on the problems found to prove that there is no difference in the SpO2 of the baby that is found, if during the monitoring process both use the combination method and CTG if it is found that the monitoring results experience early deceleration then the output is Newborns are thought to have decreased oxygen saturation (SpO2).…”
Section: Discussionmentioning
confidence: 99%